Analysis of Spatial Disparities by a Structural Equations Model - Maria Francesca Cracolici; Miranda Cuffaro; Peter Nijkamp (Tinbergen Institute, 2008)
This paper presents a new analytical framework for assessing spatial disparities among countries. It takes for granted that the analysis of a country's performance cannot be limited solely to either economic or social factors. The aim of the paper is to combine relevant economic and non-economic (mainly social) aspects of a country's performance in an integrated logical framework. Based on this idea, a structural simultaneous equation model will be presented and estimated in order to explore the direction of the causal relationship between the economic and the non-economic aspects of a country's performance. Furthermore, an exploration of the trajectory that each country has registered over time along a virtuous path will be offered. By means of a matrix persistency/transition analysis, the countries will be classified in clusters of good/bad performance. One of the most interesting conclusions concerns the inability of most countries to turn the higher educational skills of the population into greater economic performance over time. In addition, our analysis also shows that making an accurate picture record and formulating related policy aiming at environmental care is highly desirable. It is surprising that only a few countries have reached a favourable economic and environmental performance simultaneously.
Keywords: P46; 330; Socio-economic well-being; living standards; structural simultaneous equation model; Zufriedenheit; Lebensqualität; Entwicklungsindikator; Strukturgleichungsmodell; Welt